Studi tentang Kemiskinan dan Persepsi Masyarakat di Kota Pagar Alam - Junaidi Tarwiyanto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Economic growth is followed by groowing of amount poverty population, certainty invited some questions, for example: Who did actually enjoy the economic growth? Is economic growth caused by productivity growth or using production factor? Is economic growth be concentated on certain sectors while growing of some orther sector is relative slow until can’t be able to press poverty. This research aim to: explained phenomena of poverty in South Sumatra and explain the source of problem of poverty Pagar Alam City and success in doing poverty program From result of survey is known at 2007, Pagar Alam City constitute one of region in South Sumatra has smallest, Poverty depth Index, namely the third smallest after Prabumulih (0.20) and OKU (0.32), while Pagar Alam City poverty depth index: 0.34. The source pf poverty problem Pagar Alam City namely: Failure of basic right, the handling of population problem is weak and Inequality inter region.Keywords: Poverty, Population, Inequality